A detailed evaluation of surface, thermal, and flammable properties of polyamide 12/glass beads composites fabricated by multi jet fusion. (8th September 2021) - Guo, Binbin; Xu, Zhiyao; Luo, Xue; Bai, Jiaming
ABSTRACT: Multi jet fusion (MJF) is an emerging powder three-dimensional (3D) printing technology with an ultrafast printing speed, in which polyamide 12 (PA12) is the main material currently utilised. Although structurally sophisticated 3D components have been printed by MJF, there are limitations due to the high cost of printing materials and inferior performance of the printed parts. Here, PA12/glass beads (PA12/GBs) composites with improved performance were manufactured via the MJF technique. Incorporating GBs effectively regulated the dimensional accuracy. Furthermore, the composite possessed lower surface roughness and higher surface hardness than neat PA12. Thermal analysis showed that the composite exhibited an enhanced decomposition temperature (390 °C) and char yield (38.4 wt.%) compared to neat PA12. Remarkably, the incorporation of GBs did not improve the flame retardance of neat PA12. We identified the improved functionalities of PA12/GBs composites in terms of dimensional accuracy, surface, and thermal properties and analysed possible mechanisms for the observed increased flammability.